Cyclic flexural fatigue resistance of NiTi Controlled Memory and Blue Technology instruments after torsional preloading - Túlio César MODESTO (Journal of Applied Oral Science, 2018)
Abstract Objective The aim of this study was to evaluate the influence of torsional preloading on the cyclic flexural fatigue resistance of thermally treated NiTi instruments. Material and Methods Ten new instruments New Hyflex CM (HF 30.06; Coltene/Whaladent Inc.), Typhoon CM (TYP 30.06; Clinician's Choice Dental Products) and Vortex Blue (VB 30.06; Dentsply Tulsa Dental) were chosen, based on geometry and specific characteristics of the manufacturing process. The new instruments of each system were tested in a bench device to determine their fatigue resistance through mean value of number of cycles to failure (Nf) (Control Group – CG). Another group of 10 new HF, TYP and VB instruments were submitted to 20 cycles of torsional straining between 0° and 180° (Experimental Group – EG) and then submitted to fatigue until rupture under the same conditions of the CG. Tested instruments were examined by scanning electron microscopy (SEM). Data were analyzed using one-way analysis of variance and post hoc Tukey’s test (α=.05). Results Higher fatigue resistance was accomplished by HF instruments, followed by VB and TYP (p<0.05). During the torsional preloading, the lowest mean torque value was observed for TYP instruments (p<0.05). The torsional preload caused a significant reduction in the Nf values (p<0.05) of about 20%, 39% and 45% for instruments HF, VB and TYP, respectively. Longitudinal cracks, generated during the torsional preloading, were present in VB files, but were not observed in the CM instruments (HF and TYP). Conclusions In conclusion, the flexural fatigue resistance of thermally treated instruments is diminished after cyclic torsional loading.